Comprehensive quality evaluation of different types of Gardeniae Fructus (Zhizi) and Shuizhizi based on LC-MS/MS - Qian, Huimin; Hu, Yan; Wang, Zhiwei; Ren, Aoyu; Zhang, Haiwen; Chu, Shanshan; Peng, Huasheng (Frontiers in Plant Science, 2024)
Gardeniae Fructus (Zhizi) serves as both a medicinal and edible substance and finds widespread use in various industries. There are often two kinds of medicinal materials in the market: Zhizi and Shuizhizi. Typically, Zhizi with small, round fruit is used for medicinal purposes, while Shuizhizi, characterized by large, elongated fruit, is employed for dyeing. Market surveys have revealed a diverse range of Zhizi types, and modern research indicates that Shuizhizi contains rich chemical components and pharmacological activities. In this study, we collected 25 batches of Zhizi and Shuizhizi samples, categorizing them based on appearance into obovate and round fruits, with seven length grades (A-G). Using the ultra-high performance liquid chromatography coupled with triple quadrupole mass spectrometry (UHPLC-QQQ-MS/MS) method, we simultaneously quantified 13 main chemical components in Gardenia species. In addition, we compared the weight percentage of the pericarp, flesh, and seeds parts of samples with different traits, and quantified 13 chemical components in different parts. Results indicated that, aside from a few instances of overlapping fruit size ranges, Shuizhizi generally exhibits larger and longer dimensions than Zhizi. The weight 2 proportion of the Shuizhizi pericarp is often higher than that of the Zhizi pericarp. Quantitative results highlighted significant differences in the chemical component content between Zhizi and Shuizhizi, with Shuizhizi generally containing higher levels of iridoids. The PCA and OPLS-DA analysis distinctly divided Shuizhizi and Zhizi, among which three iridoids, two organic acids, and one flavonoids made significant contributions to their classification. Cluster heatmap analysis also demonstrated complete separation between Zhizi and Shuizhizi, with clear distinctions among Zhizi samples from different origins. The distribution of the 13 chemical components in different Zhizi and Shuizhizi parts remained consistent, with iridoids and pigments concentrated in the seeds and flesh, and organic acids and flavonoids enriched in the pericarp. In summary, this study contributes valuable insights for classifying Zhizi and offers guidance on the rational use of Shuizhizi and the different parts of Zhizi.